Glomus tumor of right forearm with surgical excision: a rare case report - Patil, Swapnil A.; Nikam, Rahul M.; Sonawane, Ratnadip S.; Akre, Ajinkya H.; Shaji, Febin M. (International Journal of Research in Medical Sciences, 2024)
Glomus tumors are rare, benign, and vascular neoplasm of the glomus body, accounting <2% of all soft tissue tumors. The most common site is the subungual region of the fingers and toes. Extradigital sites, including the forearm, are uncommon and usually misdiagnosed because of their rarity and nonspecific presentation. Diagnosis is often delayed due to low level of suspicion. A strong clinical suspicion, magnetic resonance imaging, and a properly planned surgery remain the treatment. We report a 42 year old male presented with painful right forearm swelling for the last 1 years who had undergone surgical excision.